THE PERCEPTIONS OF THE USE OF QRIS ELECTRONIC MONEY ON THE MILLENIAL GENERATION IN DKI JAKARTA - Ichsan Nur Yasar (MANAJEMEN DEWANTARA, 2022)
The study was conducted to analyze the perceptions (maslahah, ease of use, word of mouth, and risk) that influence the decision to use QRIS electronic money in the millennial generation in DKI Jakarta. The research method uses a quantitative descriptive approach with a sample of 96 millennial generation respondents who know and have experience using QRIS electronic money. The sample is determined by non-probability (accidental sampling). The data were statistically analyzed using the IBM SPSS Statistics software version 28. The results showed that there was a simultaneous and partial significant effect on the variables of perception of maslahah, ease of use and risk on the decision to use QRIS electronic money in the millennial generation in Jakarta, but the perception of word of mouth generally partial effect is not significant.